Relationships Developed Abroad: Impacts on Learning During a Short-term Field Study in Italy - Brittany Marie Davis; Joellen E Coryell (Adult Education Research Conference, 2017)
This study examines graduate student’s experiences with personal relationships developed during a short-term international field study in Italy and how these relationships enhanced their learning abroad.
Keywords: relationships abroad; international field study